Clinical cases of paronychia infection: A narrative review - Sadina Tahara Jusivani; Indah Kusuma Wardani; Tiara Rahayu; Nastiti Intan Permata Sari; Fumito Maruyama (International Journal of Applied Mathematics, Sciences, and Technology for National Defense)
Paronychia is an infection that occurs in the nail fold and the barrier between the nail and cuticle, is usually caused by penetrating trauma, which allows pathogens to infect and cause damage. The infection is caused by chemical factors, such as fungi, viruses, and bacteria, and risk factors, such as occupation, allergies, and finger-biting habits. Paronychia is a common nail infection that can significantly impact quality of life and work productivity, especially in certain occupations. Paronychia infection was differentiated by two categories, acute and chronic infection. The lack of knowledge regarding the prevention, cure, and rehabilitation of paronychia infection in Indonesia is the cause of the increasing cases of this infection. This review aims to provide knowledge for the Indonesian public and an opportunity for health workers to explore paronychia cases in Indonesia. The data in this paper were retrieved from 32 articles from 2014 - 2024 from PubMed, Cochrane, and Scopus. Articles were selected based on relevance to clinical cases of paronychia in humans, focusing on diagnosis, treatment and outcomes. Then, evaluate the causes, diagnosis, and treatment of paronychia using narrative review. Found that acute paronychia results from trauma or infection, while chronic cases are often caused by fungi. Treatment in acute paronychia is done with warm soaks and oral antibiotics, while chronic requires long-term topical corticosteroids and antifungal treatments. This review analyzes clinical cases of acute and chronic paronychia to evaluate their causes, diagnosis, and treatment. Further research is needed to advance the knowledge and treatment of paronychia infections.